2014
DOI: 10.1002/tea.21160
|View full text |Cite
|
Sign up to set email alerts
|

Ethnically diverse students' knowledge structures in first‐semester organic chemistry

Abstract: Chemistry courses remain a challenge for many undergraduate students. In particular, firstsemester organic chemistry has been labeled as a gatekeeper with high attrition rates, especially among students of color. Our study examines a key factor related to conceptual understanding in science and predictive of course outcomes-knowledge structures. Previous research on knowledge structures has focused on differences between experts and novices. Given the increasing ethnic diversity of college classrooms and resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
1
16
0
7
Order By: Relevance
“…En el ámbito educativo, como estrategia de enseñanza/aprendizaje, los mapas conceptuales, además de emplearse para planificar la enseñanza (Guruceaga y González, 2004;Nousiainen, 2012), se utilizan también para: identificar ideas previas, externalizar y obtener el conocimiento conceptual de los estudiantes (Derbentseva, Safayeni, y Cañas, 2007;Chang, 2007;Brandstädter, Harmsa, y Großschedl, 2012), organizar, sintetizar y comunicar lo que saben los alumnos, captar las relaciones entre contenidos que establece el alumnado (Lopez et al, 2014), auxiliar a los alumnos a…”
Section: Revista Complutense De Educaciónunclassified
See 2 more Smart Citations
“…En el ámbito educativo, como estrategia de enseñanza/aprendizaje, los mapas conceptuales, además de emplearse para planificar la enseñanza (Guruceaga y González, 2004;Nousiainen, 2012), se utilizan también para: identificar ideas previas, externalizar y obtener el conocimiento conceptual de los estudiantes (Derbentseva, Safayeni, y Cañas, 2007;Chang, 2007;Brandstädter, Harmsa, y Großschedl, 2012), organizar, sintetizar y comunicar lo que saben los alumnos, captar las relaciones entre contenidos que establece el alumnado (Lopez et al, 2014), auxiliar a los alumnos a…”
Section: Revista Complutense De Educaciónunclassified
“…27 Núm. 3 (2016) 1247-1269 reflexionar sobre su estructura cognitiva y el proceso de producción del conocimiento (Novak y Gowin, 1988), analizar la estructura los libros de texto (Lloyd, 1990), explicitar la planificación docente, seleccionar contenidos de enseñanza y evaluar los conocimientos de los alumnos (McClure, Sonak, y Suen, 1999;Nesbit y Adesope, 2006;Assaraf y Orion, 2010;Lopez et al, 2014) entre otras aplicaciones. Hay que destacar que Núñez y Banet (1997) utilizaron los mapas conceptuales específicamente en la formación de maestros y concretamente se centraron en el tema de la nutrición humana.…”
Section: Revista Complutense De Educaciónunclassified
See 1 more Smart Citation
“…Vanides et al (2005) used a four-level rubric to evaluate the quality of the propositions in the relational scoring method. Lopez et al (2014) investigated the influence of prior science achievement and ethnicity on students' knowledge structure using Vanides et al (2005)'s proposition scoring system. Scoring propositions provided them quantitative information about the accuracy of students' knowledge structure.…”
Section: Evaluating Concept Mapsmentioning
confidence: 99%
“…Similar to differences based on gender, research with concept inventories has found that some questions appear to disadvantage students who are blind, based on their experiences [106]. Across disciplines, it is clear that prior experiences matter and can misrepresent student understanding [107].…”
Section: Discussionmentioning
confidence: 98%